Effects of graphene nanoplatelets on crystallization, mechanical performance and molecular dynamics of the renewable poly(propylene furanoate). (17th February 2020) - Papadopoulos, Lazaros; Klonos, Panagiotis A.; Tzetzis, Dimitrios; Papageorgiou, George Z.; Kyritsis, Apostolos; Bikiaris, Dimitrios N.
Abstract: Poly(propylene furanoate), PPF, is a new bio-based polyester produced from renewable resources and belongs in a class of materials expected to replace their fossil-based homologues. Envisaging its future applications, critical is the optimization of the material properties such as the mechanical performance. The latter is strongly connected with the degree of polymer crystallinity, CF, which in the case of PPF is rather slow. As in previous work in semicrystalline polymers, in order to facilitate crystallization we introduce here graphene nanoplatelets at the amounts of 0.5, 1.0 and 2.5 wt% as fillers into the PPF matrix. The study involves measurements by calorimetry (DSC), X-ray diffraction (XRD), nanoindentation testing and dielectric spectroscopy (BDS) on samples in the amorphous (melt quenched) and semicrystalline (annealed) states. DSC confirmed the aimed facilitation of crystallinity, as the crystallization time of PPF at the relatively mild temperature of 100 °C is significantly reduced in the nanocomposites. In next, we were able to estimate the rigid amorphous fraction, RAF, in the two polymer states, i.e. the interfacial polymer due to the fillers and around the formed crystals. The filler addition results in direct improvement of the mechanical performance of the amorphous samples (increase in the elastic modulus and hardness); whereas, upon the additional involvement of crystallization the mechanical properties are improved further. Interestingly, these improvements were found to correlate quite well with the amounts of formed RAF and CF. In addition, we proceed with the exploration of molecular dynamics (local β and segmental α relaxations) of PPF in the bulk and in the presence of the nanofillers, of polymer crystals as well as of introduced water traces. The severe effects on molecular dynamics were found, as expected, to arise from crystallization rather than by the fillers themselves. Results on segmental mobility (calorimetric and dielectric glass transition) were connected to the expected alternations in the semicrystalline morphology, the latter being partially supported by XRD. Finally, in the nanocomposites, an additional filler-induced relaxation was recorded ( α f ) which demonstrates independency from crystallization, however being influenced by the aforementioned water traces. Most possibly, α f arises from the polymer located at the fillers' surface. Graphical abstract: Image 1 Highlights: Renewable PPF PNCs reinforced with graphene studied by DSC, XRD, NanoIndentation and BDS. Graphene increases the crystallization rate; semicrystalline morphology alternations being found. Improved mechanical performance of PNCs, correlating well with interfacial RAF and CF amounts. Segmental dynamics and glass transition governed by crystallization; not by the filler loading. Additional filler-related dynamics arising from the interfacial layer and implemented water traces.